THE EFFECT OF SEAWEED (Eucheuma Cottonii) SUBSTITUTION ON THE CHARACTERISTICS OF TILAPIA (Oreochromis Niloticus) NUGGETS - Nadia, Nadia; Hafizah, Ellyna; Istyadji, Maya (INTERNATIONAL JOURNAL ON ADVANCED TECHNOLOGY, ENGINEERING, AND INFORMATION SYSTEM, 2023)
Tilapia nuggets are an instant food with high protein and mineral content. Adding tapioca flour to the nuggets increases gel rigidity when cooling, making the texture harder. However, to optimize the nutritional value and texture of tilapia nuggets, seaweed can be added. This study aimed to determine the best formulation for tilapia nuggets that meet SNI 7758 quality standards. Research methods included observation, literature study, questionnaire, and experiment. The results show that substituting Eucheuma Cottonii seaweed for tapioca flour significantly improved sensory, physical, and chemical test parameters. The best formulation, N1, with an effectiveness index value of 77.1, met the quality standards of SNI 7758. It received an appearance score of 7.73, odor score of 7.40, taste score of 7.73, texture score of 7.33, texture hardness of 666 gr, water content of 59.95%, ash content of 2.31%, protein content of 13.94%, and fat content of 0.76%. Therefore, adding seaweed to the formulation of tilapia nuggets can enhance their nutritional value and texture.